Pengembangan Kurikulum Pendidikan Agama Islam Sebagai Upaya Memperkuat Nilai-Nilai Keagamaan - Achmad Junaedi Sitika; Mifa Rezkia Zanianti; Mita Nofiarti Putri; Muhamad Raihan; Hurul Aini; Illa Nur’Aini; Kedwi Walady Sobari (Departement of Mathematics Education, 2023)
Abstract Curriculum is one of the important tools in education. The curriculum has a central position in realizing the educational goals and objectives that are aspired to. The curriculum itself is a set of plans and arrangements regarding objectives, content and learning materials, to achieve certain educational goals. The Islamic education curriculum must start from the preparation or formulation of educational goals according to Islam. The aim of education according to Islam is the realization of kaffah Muslims, namely Muslims who (1) are physically healthy and strong; (2) his mind is smart and clever: (3) his heart is filled with faith in Allah. The development of these aspects must be balanced. The development of the Islamic Religious Education (PAI) curriculum has undergone a paradigm shift, although some of the previous paradigms have been maintained until now. Values in Islam contain two categories of meaning from a normative perspective, namely considerations of good and bad, right and wrong, right and wrong, blessed. and cursed by Allah SWT. This research can provide concrete recommendations to improve the Islamic Religion education curriculum, so that students can have a deeper understanding of Islamic teachings and are able to practice religious values in everyday life.